2022
DOI: 10.1021/acschemneuro.1c00696
|View full text |Cite
|
Sign up to set email alerts
|

Novel Macrocyclic Antagonists of the Calcitonin Gene-Related Peptide Receptor: Design, Realization, and Structural Characterization of Protein–Ligand Complexes

Abstract: A series of macrocyclic calcitonin gene-related peptide (CGRP) receptor antagonists identified using structure-based design principles, exemplified by HTL0028016 (1) and HTL0028125 (2), is described. Structural characterization by X-ray crystallography of the interaction of two of the macrocycle antagonists with the CGRP receptor ectodomain is described, along with structure–activity relationships associated with point changes to the macrocyclic antagonists. The identification of non-peptidic/natural product-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 40 publications
(91 reference statements)
0
17
0
Order By: Relevance
“…Compound 1 is a highly potent CGRP antagonist (p K b 9.6), and its corresponding diasteroisomer ( 2 ) in which the spiro center stereochemistry is reversed is ca. three orders of magnitude less potent, which we ascribed to the stereospecificity of the ligand–receptor interaction . In addition, we also reported that the analogue of 1 in which the nicotinamide nitrogen is replaced with a CH in the corresponding spiroindene (HTL0029881, 3 ) exhibits a modest comparative reduction in potency (p K b 8.9)…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…Compound 1 is a highly potent CGRP antagonist (p K b 9.6), and its corresponding diasteroisomer ( 2 ) in which the spiro center stereochemistry is reversed is ca. three orders of magnitude less potent, which we ascribed to the stereospecificity of the ligand–receptor interaction . In addition, we also reported that the analogue of 1 in which the nicotinamide nitrogen is replaced with a CH in the corresponding spiroindene (HTL0029881, 3 ) exhibits a modest comparative reduction in potency (p K b 8.9)…”
mentioning
confidence: 70%
“…Functional CGRPR antagonist potencies, i.e., pK b values, of the compounds were determined according to previously reported methods. 11,16 Purified MBP-RAMP1 ECD-CLR ECD fusion protein samples bound to 3, 4, and 10 were prepared according to previously reported methods. 11,16 Data and refinement statistics are listed in the Supporting Information (pp 2 and 3).…”
mentioning
confidence: 99%
See 3 more Smart Citations